Efforts to Improve Student Learning Outcomes with Performance Assessment on the Concept of Environmental Pollution - Deden Muhamad Nurdin (International Journal of Learning Media on Natural Science (IJLENS), 2025)
This research is motivated by the low value of student learning outcomes seen from the average value of mid-term exams and daily tests of students in biology subjects is 70, while the minimum completeness criteria value that must be achieved is 75. Based on this, researchers are interested in conducting learning that applies performance assessments to improve student learning outcomes. Performance assessments are used because they are authentic and comprehensive assessments whose final results will improve students' cognitive potential better. The purpose of this study was to determine the increase in student learning outcomes with performance assessments. The research method used was a weak experiment. The research instruments used were a performance assessment rubric and a post-test of student learning outcomes. The subjects in this study were grade X students at SMAN 1 Singaparna with a sample selected using the cluster random sampling technique of 37 people. Based on the results of the research and discussion in this study, it can be concluded that there was an increase in the learning outcomes of grade X students after the implementation of performance assessments. The implications of performance assessments have a significant effect on student learning outcomes in the moderate category.